Efficacy of a Single Preoperative Dexamethasone Dose to Prevent Nausea and Vomiting After Thyroidectomy (the tPONV Study): A Randomized, Double-blind, Placebo-controlled Clinical Trial. Issue 6 (December 2015) - Tarantino, Ignazio; Warschkow, Rene; Beutner, Ulrich; Kolb, Walter; Lüthi, Andreas; Lüthi, Cornelia; Schmied, Bruno M.; Clerici, Thomas
Abstract : Objective: Does dexamethasone given before thyroidectomy reduce postoperative nausea and vomiting (PONV) in a randomized controlled trial? Background: PONV is an unsettling problem that commonly occurs in patients after thyroidectomy. Various preventive measures have been studied; however, many of these studies have been criticized for their biases (eg, use of opioids, sex selection) or were even retracted. Methods: This single-institution, randomized, double-blind, placebo-controlled, superiority study was performed between January 1, 2011, and May 30, 2013. Patients undergoing thyroidectomy for benign disease were allocated by a block randomized list to receive a preoperative single dose of dexamethasone (8 mg) or placebo. Patients and staff were blinded to the treatment assignment. The primary endpoint was the incidence of PONV assessed at 4, 8, 16, 24, 32, and 48 hours after surgery. To observe an incidence reduction of 50%, a total of 152 patients were required for the study. Results: The total incidence of PONV was reported in 65 of 152 patients (43%; 95% confidence interval [CI], 35–51). In the intention-to-treat analysis, PONV occurred in 22 of 76 patients (29%; 95% CI, 20–40) in the treatment arm and in 43 of 76 patients (57%; 95% CI, 45–67) in the control arm ( P  = 0.001; odds ratio = 0.31; 95% CI, 0.16–0.61; absolute risk reduction = 28%; 95% CI, 12–42). The number needed to treat was 4. No severe dexamethasone-related adverse events were observed during the study. Conclusions: A single dose of preoperative dexamethasone administration is an effective, safe, and economical measure to reduce PONV incidence after thyroidectomy.